Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/519854
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Starch Contents of Native and Heat‐Moisture Treated Jackfruit Seed Starch

Abstract: Native jackfruit seed starch (JFS) contains 30% w/w type II resistant starch (RS2) and can potentially be developed as a new commercial source of RS for food and pharmaceutical application. Heat-moisture treatment (HMT) was explored as a mean to increase RS content of native JFS. The effect of the conditions was tested at varied moisture contents (MC), temperatures, and times. Moisture levels of 20–25%, together with temperatures 80–110°C, generally resulted in increases of RS amount. The highest amount of RS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
6
19
0
7
Order By: Relevance
“…Crosslinking of CMS has been performed to produce hydrogels for potential application in metal ions removal from water [3,4], as pharmaceutical gelling agent and emulsion stabilizer [5], tablet disintegrant [6], or for drug delivery systems [7,8]. The crosslinking agents were dichloroacetic acid [4,5], phosphorous oxychloride [3], epichlorohydrin [9], sodium trimetaphosphate [10], or polyfunctional carboxylic acids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking of CMS has been performed to produce hydrogels for potential application in metal ions removal from water [3,4], as pharmaceutical gelling agent and emulsion stabilizer [5], tablet disintegrant [6], or for drug delivery systems [7,8]. The crosslinking agents were dichloroacetic acid [4,5], phosphorous oxychloride [3], epichlorohydrin [9], sodium trimetaphosphate [10], or polyfunctional carboxylic acids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Amylose contents of jackfruit seed RS exhibited a correlation trend with RS content. Jackfruit seed treated with heat-moisture treatment with higher RS demonstrated less swelling, while the solubility remained unchanged [45]. In addition, Madruga et al [12] observed that the swelling power and solubility of jackfruit seed starch increased with increase in temperature, showing opaque pastes.…”
Section: Jackfruitmentioning
confidence: 99%
“…The jackfruit seeds have been well documented to contain an average of above 60% dry basis of starch [44]. Native jackfruit seed can contain a reasonable amount of type II RS due to its relatively high amylose content 24-32% [45]. Jackfruit seed starch is widely used in many manufactured food products as it provides a gelling property that is suitable for various baked products [46].…”
Section: Jackfruitmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Moreover, its aqueous solutions can be used as binders for sand foundry [3][4][5] wood, [6] drilling mud, [7,8] DOI: 10.1002/star.201900240 or production of electrorheological fluids. [9,10] Viscosity of CMS solutions is a very important factor in many applications and it can be regulated by, for example, optimization of starch etherification parameters, [11,12] slight crosslinking [13,14] or additive incorporation, for example clays, into solutions. [13,15] CMS is safe and non-toxic, so it can be used for cosmetics or medicine.…”
Section: Introductionmentioning
confidence: 99%